ANALYSIS OF APPLICATION OF LEARNING THEORY ACCORDING TO COGNITIVE FLOW IN LEARNING MATHEMATICS AT SD IN ACTIVITIES OF CAMPUS TEACHING 4 - Arlina Yuza; Neviyarni; Susi Herawati; Eni Desfitri; Harun, Gustiayu Juita (Study program PGSD FKIP Universitas Bung Hatta, 2023)
The application of Jean Piaget's cognitive learning theory can assist students in obtaining and processing information received, both in life and in implementation in the learning process of mathematics, especially numeracy skills. However, based on the results of observations made while accompanying students in the teaching campus program 4, it was obtained an overview of the learning situation of students who had not been able to provide sufficient knowledge in mathematical numeration, high-class students still had not memorized multiplication, and a lack of student interest in learning so that in this study the researcher discussed how the application of learning theory according to the cognitive flow in learning mathematics on-campus teaching activities 4. This study used a qualitative research approach with a case study type of research. Results The application of learning theory according to the cognitive flow in the teaching campus program 4 obtained a success percentage of 80% in increasing students' multiplication abilities with an aspect ratio of 8 out of 10 students. Provision of additional learning has a success percentage of 70% in improving students' numeracy skills and spatial planning has a success percentage of 100% to provide a comfortable situation during the learning process. Success is obtained because in its implementation teaching campus students to provide treatment according to the developmental stage of the student's age according to suggestions cognitive aspect of learning theory according to Piaget